LA PRAETERITIO PROEMIAL DE LA TEBAIDA DE ESTACIO. ¿VOCACIÓN CÍCLICA O VIRGILIANISTA? - Criado, Cecilio (Myrtia, 1999)
This paper reviews and discusses the theories of some critics, who had suggested that the Statius's proemium is a clear programmatic declaration and in the same way they had interpreted the praeteritio of this prolog as a anticlicic manifestation against Antimacus of Colophon. Therefore, the critics considered that Statius takes side on the classicism of Vergilius.